Pengaruh Kualitas Layanan Transportasi Laut terhadap Kepuasan Pelanggan pada Jasa Bongkar Muat PT. Pelindo IV Cab. Makassar - Irman Irman (Journal on Education, 2023)
The purpose of this study is to determine the factors that influence customer satisfaction with the loading and unloading services of PT. Pelindo Cab. Makassar. This study analyzes how the quality of service consisting of security, \timeliness, facilities/ infrastructure, and its effect on customer satisfaction. This survey was responded to by 55 customer companies, consisting of shipping companies (shipping companies), ship cargo expeditions (EMKL/PPJK), and other shipping companies. The sampling technique used is random sampling, data is analyzed using simple linear regression. The results showed that there was a positive and significant influence between service quality variables on customer satisfaction.